PENGARUH KECERDASAN EMOSI TERHADAP PENYESUAIAN SOSIAL REMAJA DI PONDOK PESANTREN - Sulistio, Widyana; Wiroko, Endro Puspo; Paramita, Anindya Dewi (Jurnal Psikologi, 2018)
The aim of study is to determine the effect of emotional intelligence on social adjustment in adolescents at boarding school. This study uses a quantitative approach with data collection techniques using questionnaires. Respondents in this study are junior high school adolescent in boarding school, amounting to 155 people with age range 11-14 year. The sampling technique used is purposive sampling. This study uses two instruments namely, the scale of social adjustment and the scale of emotional intelligence. Based on calculation result with simple linear regression using SPSS version 20.0 for windows obtained R2 equal to 0,079 with significance 0,000 (p <0,05), proven there is influence between emotional intelligence to social adjustment in adolescence equal to 7,9% and the rest influenced by other factor . The results of this study showed that emotional intelligence significantly give effect to adolescent social adjustment in boarding school. In this study also known the value of social adjustment and adolescent emotional intelligence in boarding schools are at a moderate level.Â Keywords: social adjustment, emotional intelligence, adolescence